A Victorian Educational Pioneer’s Evangelicalism, Leadership, and Love - Phipps, Pauline A. author. aut Link
XIII, 165 p. 15 illus.
Keywords: ‘A wonderful case and perfect for a microhistorical approach. Pauline A. Phipps deals with an important story of an unknown educational pioneer – Constance Louisa Maynard – who had a wide range of expertise that shaped her focus in life, both professional and personal. Phipps has great source material to work with, and she brings to light important issues through her research that speak to modern readers; race, patriotism, scientific conduct, and so on.’ – Sigurður Gylfi Magnússon, University of Iceland, Iceland This book examines the relatively unknown English late-Victorian educational pioneer, Constance Louisa Maynard (1849-1935), whose innovative London-based Westfield College produced the first female BAs in the mid-1880s. An atypical and powerful woman, Maynard is also notable for her unique knowledge of psychology and patriotic Evangelicalism, both of which profoundly shaped her ambitions and passions. In contrast to most history about an individual’s life, this book builds a fascinating life story based upon evidence and clues from minutia. The focus is on nine enigmatic actions motivated by Maynard in her quests for educational leadership, global conversion, and same-sex love. Maynard’s acts that she called “mistakes,” caused deep enmities with administrators and college women. Yet amid her trials and conflicts Maynard made key decisions about her public and private life. Moreover, her so-called mistakes reveal astonishing new insights into a past mindset and the rapidly changing world in which Maynard lived. Pauline A. Phipps is retired from teaching in History and Women’s and Gender Studies at the University of Windsor, Canada. Author of Constance Maynard’s Passions: Religion, Sexuality, and an English Educational Pioneer 1849-1935 (2015), Phipps has also published in journals such as The History of Sexuality and Women’s History Review.